A scanless method for terahertz time-domain imaging - Zanotto, Luca; Balistreri, Giacomo; Rovere, Andrea; Kwon, O. Pil; Morandotti, Roberto; Piccoli, Riccardo; Razzari, Luca (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2023)
Terahertz (THz) time-domain imaging can uncover the spectral fingerprints of materials, detect changes in both refractive index and absorption, and reveal the inner structure of complex objects through time-of-flight measurements. Despite its potential, the lengthy acquisition typically required to spatially raster-scan the object and record the terahertz temporal waveforms for each spatial point limits practical applications. Our scanless imaging method sets the path for an unprecedented reduction of both system complexity and acquisition time, by addressing this crucial bottleneck. By judiciously exploiting natural wave diffraction, time-to-space encoding is applied to THz point detection and enables a nearly instantaneous capture of the terahertz waveforms. Multidimensional images are then reconstructed through a computational method. This approach opens the route for next-generation fast and compact THz imagers that are well-suited for high-repetition-rate laser sources.
Keywords: Complex objects; Inner structure; Raster scans; Scanless; Spatial points; Spectral fingerprints; Temporal waveforms; Tera Hertz; Time-domain imaging; Time-of-flight measurements